Analysis of mutable exons of neurofibromatosis Type 1 (NF1) gene in Iranian patients - Nafiseh Farhadi-Shaheni; Fahimeh Baghbani-Arani; Masoumeh Mahdavi-Ortakand (Fiyz̤, 2023)
Background: Neurofibromatosis Type 1 (NF1) is an autosomal dominant disease caused by mutations in a tumor suppressor protein called neurofibromin. The NF1 gene consists of 60 exons and due to the large size of the NF1 gene, variation in mutations and the absence of mutation hotspots is a complex problem in genetic counselling. Considering that determining the frequency of mutations in a population contributes to effective genetic counseling and prevention of more diseases. So, this study aimed to identify the underlying genetic defect in 10 Iranian patients with neurofibromatosis type 1. Materials and Methods: After collecting blood from patients and genomic DNA extraction, 9 high mutability exons were analyzed by PCR and sequencing methods. Finally, sequenced exons and reference exons were compared using the bioinformatic tools, and mutations were identified. Results: Among 10 evaluated patients six different mutations were detected. These mutations included two deletions (c.1458-1459 delAA, c.1541-1542 delAG in 13 & 14 exons, respectively), and four substitution mutations. The c.5172 G>A, c.3871-2 A>G, and c.3867 C>T mutations were reported for the first time in this study. Conclusions: The results of this study implied that there are various mutations in this disease and the most reliable method for NF1 mutation analysis is DNA sequencing.